(untitled) (Plant Tissue Culture and Biotechnology, 2026)
Arundina graminifolia (D. Don.) Hochr., commonly known as the bamboo orchid, is a terrestrial orchid of significant medicinal and ornamental value native to the Chittagong Hill Tracts (CHT) of Bangladesh. To establish an efficient conservation strategy, in vitro asymbiotic seed germination and successful root induction protocols were developed. Mature green capsules were cultured on four basal media viz. Knudson C (KC), MS, Phytamax (PM) and Vacin and Went (VW), at both half and full strengths, with or without plant growth regulators (PGRs). Full-strength PM medium supplemented with 0.5 mg/l 6-Benzylaminopurine (BAP) and 0.5 mg/l α-Naphthalene acetic acid (NAA) produced the highest germination percentage (93.34 ± 1.96%) and the shortest initiation time (6.21 ± 0.22 weeks). Subsequent seedling development, including protocorm formation and differentiation of leaf and root primordia, was significantly faster on this medium compared to MS, VW or KC. For the induction of a robust root system, elongated seedlings were transferred to half-strength MS medium supplemented with various auxins. The combination of 1.0 mg/l Indole-3-butyric acid (IBA) and 1.0 mg/l NAA proved most effective, producing the maximum number of roots (4.17 ± 0.31) and root length (3.91 ± 0.04 cm) within 30 days. Following a stepwise acclimatization process, 81.67% of the seedlings survived and were successfully established in the ex vitro environment. Statistical analysis confirmed the superiority of PM for germination and of auxin-supplemented ½MS for rooting. This protocol provides an effective method for mass propagation of this orchid. Plant Tissue Cult. & Biotech. 35(2): 399-406, 2025 (December)